Development of a new sediment flux model – Application in Chesapeake Bay. (June 2020) - Wang, Zhengui; Chai, Fei; Brady, Damian
Highlights: New sediment flux model was described with a simple structure and fewer parameters. A new decay scheme for sediment organic matter was proposed based on bacterial growth. A new method in estimating the depositional fluxes of particulate organic matter was proposed. The model was successfully implemented in Chesapeake Bay. Abstract: Sediment biogeochemical processes impact pelagic ecosystems when the sediment receives particulate organic matter (POM) deposited from the water column above, consumes dissolved oxygen, and returns inorganic nutrients to the bottom water. However, an easy-to-apply sediment model is still lacking for pelagic biogeochemical modeling. In this study, we proposed a mass conservative, process-based and easy-to-apply sediment flux model (SFM) that endeavors to simplify Di Toro (2001)'s sediment flux model (DSFM) while maintaining the ability to model sediment fluxes in multiple environments (e.g., anoxic, normoxic, variable salinity, high and low organic matter deposition, etc.). It adopts a vertically integrated approach, and has a relatively simple structure with limited number of parameters. The mineralization scheme for POM is based on bacterial growth, which can resolve the diagenesis processes on different timescales. The inhibition effects of oxygen on denitrification of NO3 and desorption of PO4 are modeled using exponential functions. This new SFM is then implemented in the Chesapeake Bay to simulate sediment oxygen demand (SOD) and sediment NH4 /NO3 /PO4 /Silica fluxes across the sediment–water interface. To estimate POM depositional fluxes from the water column, a new method is introduced that links surficial sediment and bottom-water POM concentrations. Further integration of this method into the SFM turns the model calibration into a mass conservative and self-consistent process, which is well constrained by observations. The modeled sediment fluxes from the new SFM match observations across seasons and stations with correlation coefficient ranging from 0.3 to 0.7. The successful application of SFM in Chesapeake Bay and subsequent analysis show that the new SFM has many advantages including mass conservation, high temporal resolution, relatively simple structure, and easy implementation. The SFM is a good tool for linking pelagic ecosystem models to sediment biogeochemical processes.